Knowledge about dietary fibre: a fibre study framework - Guiné, Raquel (2016)
The objective of this work was to study the degree of knowledge about dietary fibre (DF), as influenced by factors such as gender, level of education, living environment or country. For this, a descriptive cross-sectional study was undertaken on a non-probabilistic sample of 6010 participants from 10 countries in different continents (Europe, Africa and America). The results showed that the participants revealed on average a positive but still low global level of knowledge, which alerts for the need to take some actions to further inform the population about DF and its role as a component of a healthy diet. The results also indicated differences between genders, levels of education, living environments and countries. The highest level of knowledge was revealed by the participants from female gender, with higher education and living in urban areas. Concerning the country, the best informed were the participants from Romania, followed by those from Portugal and Turkey while the least informed were from Egypt.